Analisis Evaluasi Pengembangan E-Government di Dinas Komunikasi, Informatika dan Statistik Provinsi Bengkulu - Ema Amalia; Evi Lorita (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
This study aims to determine the results of the Evaluation of E-Government Development at the Bengkulu Province Communication, Information and Statistics Office. The method used in this research is descriptive research with qualitative data analysis. The subject of this research is the Bengkulu Province Communication, Informatics and Statistics Office which has carried out E-Government Development in the context of bureaucratic reform based on Presidential Instruction No. 3 of 2003 at the Bengkulu Province Communication, Information and Statistics Office. Data collection techniques used include: Observation, Interview, and Documentation. The results of the study show that: (1) The Bengkulu Provincial Government has made preparations in the development of e-government, namely by creating a website with the name bengkuluprov.go.id which is one of the portal websites that functions as a means of information, communication and transactions between the public and the government. can be done via the internet. (2) At the maturation stage in the development of E-Government at the Bengkulu Province Communication, Informatics and Statistics Office, two things have been done, namely the creation of an interactive and easy-to-access public information site, and the creation of interfaces with other institutions or applications that are indirectly connected. / link with websites owned by other institutions in the Bengkulu provincial government. (3) The bengkuluprov.go.id website is an application developed by the Bengkulu Provincial Government as a form of communication and information facility in improving the quality of services to the people of Bengkulu Province. (4) The bengkuluprov.go.id website is a service application by the Bengkulu Provincial Government to the people of Bengkulu Province. So that the function of providing information services by Government to Government (G2G), Government to Business (G2B), and Government to Citizen (G2C) can be carried out by the Bengkulu Provincial Government.